The Student as Political Metaphor in El Semanario de Caracas (1810–1811). Issue 5 (May 2017) - Briggs, Ronald
Abstract : Miguel José Sanz and José Domingo Díaz's El Semanario de Caracas (1810–1811) lived and died with the ill-fated first Venezuelan republic. An attorney and a member of the colonial elite, Sanz (1756–1814) tended to characterize the Venezuelan public as political beginners in need of extra instruction and to posit the Semanario as their textbook. Reading Sanz in the context of the tumultuous events and swirling opinions in Venezuela, I analyse the advantages and limitations of the student as a conceptual frame for the newly independent republic. I argue that the teacher–student gap that twentieth-century critics identified as an essential trope for the rhetoric of educational reform is embedded in the discourse of Sanz and his contemporaries. Positing himself as a political teacher who wishes to make the public see recent events from his, very different, perspective, Sanz becomes a political version of the educational reformer.